Exploring the Association Between Heart Rate Control and Rehospitalization: A Real-World Analysis of Patients Hospitalized with Heart Failure with Reduced Ejection Fraction - Freny Vaghaiwalla Mody; Ravi K. Goyal; Mayank Ajmera; Keith L. Davis; Alpesh N. Amin (Adis, Springer Healthcare, 2024)
Abstract Background In patients with heart failure with reduced ejection fraction (HFrEF), lower discharge heart rate (HR) is known to be associated with better outcomes. However, the effect of HR control on patient outcomes, and the demographic and clinical determinants of this association, are not well documented. Objectives The purpose of this work was to evaluate the association between the HR control and the risk of post-discharge rehospitalization in patients hospitalized with HFrEF. Methods Data were collected using a retrospective medical record review in the USA. Reduction in HR between admission and discharge ("HR control") defined the primary exposure, categorized as no reduction, > 0 to < 20% reduction, and ≥ 20% reduction. Time to first rehospitalization in the post-discharge follow-up defined the study outcome and was analyzed using multivariable Cox regression modeling. Results A total of 1002 patients were analyzed (median age, 63 years; median follow-up duration, 24.2 months). At admission, 59.1% received beta-blockers, 57.4% received diuretics, and 47.5% received angiotensin-converting enzyme (ACE) inhibitors. Most patients (90.5%) achieved some HR control (38.4% achieved > 0 to < 20% reduction, and 52% achieved ≥ 20% reduction). Approximately 39% were rehospitalized during the follow-up (14% within 30 days). In multivariable analysis, patients with > 0 to < 20% reduction in HR had a 39% lower risk of rehospitalization [hazard ratio 0.61; 95% confidence interval (CI) 0.43-0.85]; patients with ≥ 20% reduction in HR had a 38% lower rehospitalization risk (hazard ratio 0.62; 95% CI 0.45-0.87) than those with no HR reduction. Conclusions Reduction in HR between admission and discharge was associated with reduced risk for rehospitalization. Findings indicate HR control as an important goal in the management of patients hospitalized for HFrEF.